A performance-aware yield analysis and optimization of manycore architectures. (August 2016) - Lee, Jeong-Gun; Kwak, Sanghoon
Highlights: Asymptotic performance average yield models for manycore processors are derived. Simulation and analysis for performance average yields of manycore processors. Finding optimum manycore configurations based on simulation and analysis models. Design space exploration with different semiconductor technology parameters. Graphical abstract: Abstract: In advanced nano-scale fabrication technology, maintaining both manufacturing yield and chip reliability is a challenging issue. Recent manycore processors provide inherent core redundancy and the redundancies can be exploited to resolve the yield and reliability problems. In this paper, we develop asymptotic analysis and simulation models to better understand performance and yield joint-characteristics in a manycore processor design. Our asymptotic model is built based on Amdahl's law, Eble's rule and statistical yield equations to derive the optimum number of cores with respect to " performance-averaged yield ". Our model can predict possible impacts of different manycore processor configurations and process technology parameters on the performance average yield for given degree of parallelism. Through the asymptotic analysis and optimization based on our model, we can observe an asymptotic relationship between design parameters such as "the number of cores" and "core area" of manycore architectures with regards to its performance and yield.